Clinical Utility of Transcranial Magnetic Stimulation (TMS) in the Presurgical Evaluation of Motor, Speech, and Language Functions in Young Children With Refractory Epilepsy or Brain Tumor: Preliminary Evidence - Narayana, Shalini; Gibbs, Savannah K.; Fulton, Stephen P.; McGregor, Amy Lee; Mudigoudar, Basanagoud; Weatherspoon, Sarah E.; Boop, Frederick A.; Wheless, James W. (Frontiers in Neurology, 2021)
Accurate presurgical mapping of motor, speech, and language cortices is crucial for neurosurgical planning and minimizing post-operative functional deficits is challenging in young children with neurological disease. In such children, both invasive (cortical stimulation mapping) and non-invasive functional mapping imaging methods (MEG, fMRI) have limited success, often leading to delayed surgery or adverse post-surgical outcomes. We therefore examined the clinical utility of transcranial magnetic stimulation (TMS) in young children who require functional mapping. In a retrospective chart review of TMS studies performed on children with refractory epilepsy or brain tumor at our institution, we identified 47 mapping sessions in 36 children 3 years of age or younger in whom upper and lower extremity motor mapping was attempted and 13 children 5-6 years old in whom language mapping using a naming paradigm was attempted. The primary hand motor cortex was identified in at least one hemisphere in 33 of 36 patients, and in both hemispheres in 27 children. In 17 children, primary leg motor cortex was also successfully identified. The language cortices in temporal regions were successfully mapped in 11 of 13 patients, and in 6 of them, language cortices in frontal regions were also mapped, with most children (n = 5) showing right hemisphere dominance for expressive language. Ten children had a seizure that was consistent with their clinical semiology during or immediately following TMS, none of which required intervention or impeded completion of mapping. Using TMS, both normal motor, speech, and language developmental patterns and apparent disease induced reorganization were demonstrated in this young cohort. The successful localization of motor, speech, and language cortices in young children improved understanding the risk-benefit ratio prior to surgery and facilitated surgical planning aimed at preserving motor, speech, and language functions. Post-operatively, motor function was preserved or improved in 9 out of 11 children who underwent surgery, as was language function in all 7 children who had surgery for lesions near eloquent cortices. We provide feasibility data that TMS is a safe, reliable, and effective tool to map eloquent cortices in young children.